Design of Controller for Stable Microgrid Operation - Mehta, Sahil (My University, 2024)
Microgrids are integral to sustainable energy infrastructure, offering localized control over power generation, distribution, and consumption. Despite their multiple advantages in resilience and renewable integration, various challenges persist, particularly in maintaining stability amidst the dynamic and uncertain nature of renewable inputs like solar and wind. Thus, to address such issues, robust controllers are essential for managing uncertain renewable energy sources (RES) and ensuring stable microgrid operation. An inclusive literature survey reveals that the current literature lacks a robust controller that maintains stable microgrid operation while considering multiple system parameters such as voltage and frequency. Besides, in line with this, the literature also lacks an approach to performing strategic load shedding given load priority in the presence of uncertain RES. In addition, the literature also lacks a comprehensive approach to microgrid assessment, especially focusing on all the performance aspects, i.e., technical, economics, and implementation. Lastly, given the microgrid assessment, an ideology of a comprehensive stability assessment index is unavailable in the existing literature. Thus, focusing on such issues, this work presents a stage-wise control strategy that utilizes a fuzzy logic controller to regulate frequency and voltage in islanded microgrids. Divided into three stages, the approach manages minor perturbations with battery support and strategically sheds non-critical loads during significant perturbations to enhance stability. Additionally, a robust energy management system employing a cascaded dual-fuzzy logic-based control approach to effectively manage battery operation, microgrid mode of operation, and load distribution has also been presented. In addition, this work also presents the use of HOMER Pro software for the economic assessment of developed microgrids, considering Kibber Village, India, as an exemplary system. In addition to the economic and technical assessment, this work proposes a hardware test bench for real-time validation using a programmable logic-based controller (PLC). Lastly, considering the factor for stability assessment, this research presents a novel methodology for determining the Microgrid Stability Index (MGSI), employing a fuzzy inference system. Validation via MATLAB simulations, multiple case studies, and comparison with existing topologies demonstrate the effectiveness of the proposed approaches in ensuring stable microgrid operation.
Keywords: Microgrid Stability; Fuzzy Logic Control; Renewable Energy Integration; Energy Management System; PLC; HOMER Pro; Microgrid Stability Index (MGSI)